Jinnah : India, partition, independence - Singh, Jaswant, 1938- (Oxford ; New York : Oxford University Press, 2010)
Biography of Mohammed Ali Jinnah, 1876-1948, statesman and founder of Pakistan.
"1st pub. by Rupa & Co., New Delhi 2009"--t.p. verso.
Includes bibliographical references (p. [493]-537) and index.
Keywords: Jinnah, Mahomed Ali, -- 1876-1948.; Statesmen -- Pakistan -- Biography; Politicians -- India -- Biography. -- General; Pakistan movement; India -- Politics and government -- 1919-1947.; India -- History -- Partition, 1947.